Comparison of the initial reactant structure and crosslinked network of poly(dimethyl siloxane) membranes from different macromonomers. Issue 7 (23rd September 2014) - Singh, Puyam S.; Jadav, Ghanshyam L.; Aswal, Vinod K.; Das, Arun K.; Kumar, Sugam; Kansara, Ankit M.; Chaudhri, Sanjay G.; Brahmbhatt, Harshad
ABSTRACT Some of the best entities for the removal of volatile organic pollutants from water, poly(dimethyl siloxane) (PDMS) membranes from two types of initial PDMS precursors, were thoroughly investigated. In both the cases, the sizes of the initial macromonomers increased because of the crosslinking in the liquid state, and they exhibited Gaussian chain statistics, which were condensed by further crosslinking to the formation of the membranes. The structures of both the membrane types exhibited large interchain spacing on swelling; this implied a high degree of chain mobility. Their structural properties were corroborated by their separation performances. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41461.